Fabrication and Mechanical Properties of Aluminium-Aluminium Oxide Metal Matrix Composites - Nuruzzaman, D. M.; Siti Nur Sakinah, Jamaludin; Farah Fazira, Kamaruzaman; Basri, S.; Nur Amira Mardian, Zulkifli (IJENS Publisher, 2015)
In this research study, aluminium-aluminium oxide (Al-Al2O3) metal matrix composites (MMCs) of different percentage reinforcements of aluminium oxide were prepared. Three different types Al-Al2O3 composite specimens having 10%, 20% and 30% volume fractions of aluminium oxide were fabricated using conventional powder metallurgy (PM) route. These composite specimens were fabricated under different compaction loads 15 ton and 20 ton. The effects of volume fraction of aluminium oxide particulates and compaction load on the properties of Al-Al2O3 composites were investigated. The obtained results revealed that density and hardness of the composites are significantly influenced by volume fraction of aluminium oxide particulates. Results also showed that density, hardness and microstructure of Al-Al2O3 composites are markedly influenced depending on the compaction load. The increase in the volume fraction of Al2O3 enhances the density and hardness of the Al-Al2O3 composites. It was found that for 20 ton compaction load, the composites show increased density and hardness as well as improved microstructure than the composites prepared under 15 ton compaction load. Moreover, optical micrographs revealed that aluminium oxide particulates are almost uniformly distributed in the aluminium matrix. It was also observed that after sintering process, flat and undistorted specimens were prepared successfully.